Modern «samizdat»: the definition - E. N. Savenko (Библиосфера)
The article examines the transformation of self-publishing. A comparative analysis of the key features that characterize samizdat of the Soviet and the post-Soviet period is made. The definition that reflects the essence of the modern concept of samizdat is formulate.